2013
DOI: 10.3109/00207454.2013.856010
|View full text |Cite
|
Sign up to set email alerts
|

Forbearance for fluoxetine: Do monoaminergic antidepressants require a number of years to reach maximum therapeutic effect in humans?

Abstract: It is of high clinical interest to better understand the timecourse through which psychiatric drugs produce their beneficial effects. While a rough estimate of the time lag between initiating monoaminergic antidepressant therapy and the onset of therapeutic effect in depressed subjects is two weeks, much less is known about when these drugs reach maximum effect. This paper briefly examines studies that directly address this question through long-term antidepressant administration to humans, while also putting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…This is why fluoxetine is not suggested as a first-line treatment for migraine prophylaxis (European Federation of Neurological Societies (EFNS), American Academy of Neurology (AAN) practice guidelines). Nevertheless, the use of fluoxetine in migraine prophylaxis cannot be categorically excluded (23,43), and our study could, to some extent, explain its potential prophylactic action by shedding further light on the possible mechanism(s) involved. Our study is based on two seminal findings not specifically confirmed in this research, namely, that: (i) chronic fluoxetine increases central levels of 5-HT (44,45), although we tried somehow to mimic this effect by i.t. administration of 5-HT; and (ii) intracarotid infusions of capsaicin result in porcine carotid vasodilatation mediated by release of CGRP (16), a vasodilator neuropeptide released from capsaicin-sensitive trigeminal sensory nerves (10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is why fluoxetine is not suggested as a first-line treatment for migraine prophylaxis (European Federation of Neurological Societies (EFNS), American Academy of Neurology (AAN) practice guidelines). Nevertheless, the use of fluoxetine in migraine prophylaxis cannot be categorically excluded (23,43), and our study could, to some extent, explain its potential prophylactic action by shedding further light on the possible mechanism(s) involved. Our study is based on two seminal findings not specifically confirmed in this research, namely, that: (i) chronic fluoxetine increases central levels of 5-HT (44,45), although we tried somehow to mimic this effect by i.t. administration of 5-HT; and (ii) intracarotid infusions of capsaicin result in porcine carotid vasodilatation mediated by release of CGRP (16), a vasodilator neuropeptide released from capsaicin-sensitive trigeminal sensory nerves (10).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is based on two seminal findings not specifically confirmed in this research, namely, that: (i) chronic fluoxetine increases central levels of 5-HT (44,45), although we tried somehow to mimic this effect by i.t. administration of 5-HT; and (ii) intracarotid infusions of capsaicin result in porcine carotid vasodilatation mediated by release of CGRP (16), a vasodilator neuropeptide released from capsaicin-sensitive trigeminal sensory nerves (10).…”
Section: Discussionmentioning
confidence: 99%